CMOS-MEMS multiple resonant vibration energy harvester for wireless sensor network - Ali, I. (Institute of Electrical and Electronics Engineers Inc., 2015)
This paper presents the design, modeling, and simulation of a multiple resonant MEMS vibration energy harvester (VEH) suitable for wireless sensor network (WSN) applications. Since ambient vibration has a frequency of 100 Hz and below, a multiple resonant harvester will be an advantage to increase the vibration frequency and hence the output voltage produced by the device. The high frequency harvester is designed using CMOS technology capable of monolithically integration with any CMOS circuits. For a standard button battery size (16 Ã 16 Ã 5 mm3) harvester, simulation result shows that the harvester can provide peak voltage of 3.0 Volts at 20 Hz and 1 g vibration with a single high frequency oscillator. The series configuration of high frequency structures can provide multiple of 3.0 Volts output voltage. Â© 2015 IEEE.